Knowledge and Attitude towards Smoking among University Students in Lahore - Ali, Muhammad; Jahangir, Maria; Khan, Asaf; Faridullah, .; Hameed, Firdous (International Journal of Social Sciences and Management, 2017)
Background: Smoking is the major health problem all over the world and now it’s become trend in university students to have smoking behavior because they believed that due to smoking they will be more acceptable in friends group. The most prevalence of smoking among university students is due to the attitude of students that it could enhance their personal attributes and make a positive change in their personality. The most provoking factor in the students to start smoking was the lack of knowledge regarding the harmful effect of smoking and also the students believed that smoking can reduce stress. Objective: To assess knowledge and attitude of university students towards smoking. Methodology: A cross sectional descriptive study design was used to assess the knowledge and attitude of university students towards smoking. Sample size of 222 students were taken from three departments of The University of Lahore, in which 80 students were from Nursing, 82 from Biotechnology(IMBB) and 60 physiotherapy students were included in this study. Results: Out of 222 students 32% were current smokers while 68% were nonsmokers, 70% students believed that Nicotine in Cigarette is not addictive to human, 83% of the respondents believed that smoking is a disgusting behavior and 85% of the respondents believed that smoking should be banned in Universities significant amount of students. Conclusion: there is strong link between the students’ attitude and smoking behavior and it is important for parents and teachers to supervise their student’s behavior. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 44-54